Disruptive Mood Dysregulation Disorder and its Impact on Rates of Bipolar Disorder among Children and Adolescents - Alghamdi, Waleed A. (Current Psychiatry Research and Reviews, 2020)
Background: In 2013, Disruptive Mood Dysregulation Disorder (DMDD) was introduced in the DSM-5 in part to curb the rapid rise in the rates of bipolar diagnosis among children and adolescents during the decade before the DSM-5 publication. DMDD proved to be a controversial diagnosis for many reasons. Objective: This brief review aims to provide an overview of the DMDD diagnosis and its origins and summarize available data on the impact of the introduction of the DMDD diagnosis on the rates of bipolar disorder among children and adolescents. Methods: Multiple scientific databases were searched using the related terms “DMDD”, “Disruptive Mood Dysregulation”, and “pediatric bipolar disorder” in combination with the terms “diagnosis” and “impact”. The retrieved articles were reviewed carefully. Results: The DMDD diagnosis rates have steadily increased since its introduction. Furthermore, available data show a decrease in the rates of bipolar disorder diagnosis among children and adolescents over the past few years. Conclusion: The very limited available data since 2013 show a decline in the diagnosis of bipolar disorder among children and adolescents. More time and further research are needed to more accurately determine the impact of the DMDD diagnosis on the rates of bipolar disorder in this population.
Keywords: pediatric